Assessment of treatment response in cardiac sarcoidosis based on myocardial 18F-FDG uptake - Frischknecht, Lukas; Schaab, Jan; Schmauch, Eloi; Yalamanoglu, Ayla; Arnold, Dennis D.; Schwaiger, Judith; Gruner, Christiane; Buechel, Ronny R.; Franzen, Daniel P.; Kolios, Antonios G.A.; Nilsson, Jakob (Frontiers in Immunology, 2023)
Objective Immunosuppressive therapy for cardiac sarcoidosis (CS) still largely consists of corticosteroid monotherapy. However, high relapse rates after tapering and insufficient efficacy are significant problems. The objective of this study was to investigate the efficacy and safety of non-biological and biological disease-modifying anti-rheumatic drugs (nb/bDMARDs) considering control of myocardial inflammation assessed by 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) of the heart. Methods We conducted a retrospective analysis of treatment response to nb/bDMARDs of all CS patients seen in the sarcoidosis center of the University Hospital Zurich between January 2016 and December 2020. Results We identified 50 patients with CS. Forty-five patients with at least one follow-up PET/CT scan were followed up for a mean of 20.5 ± 12.8 months. Most of the patients were treated with prednisone and concomitant nb/bDMARDs. At the first follow-up PET/CT scan after approximately 6.7 ± 3 months, only adalimumab showed a significant reduction in cardiac metabolic activity. Furthermore, comparing all serial follow-up PET/CT scans (143), tumor necrosis factor inhibitor (TNFi)-based therapies showed statistically significant better suppression of myocardial 18F-FDG uptake compared to other treatment regimens. On the last follow-up, most adalimumab-treated patients were inactive (n = 15, 48%) or remitting (n = 11, 35%), and only five patients (16%) were progressive. TNFi was safe even in patients with severely reduced left ventricular ejection fraction (LVEF), and a significant improvement in LVEF under TNFi treatment was observed. Conclusion TNFi shows better control of myocardial inflammation compared to nbDMARDs and corticosteroid monotherapies in patients with CS. TNFi was efficient and safe even in patients with severely reduced LVEF.